Hubungan Komunikasi Interpersonal Guru dan Siswa terhadap Motivasi Belajar Siswa SMA PGRI 4 Kota Padang - Irdam (Psyche 165 Journal, 2023)
Every child has the right and obligation to receive education. Teachers and students are two important elements in realizing quality education. Education is important to improve human quality in accordance with the changes and developments of the times. Education is a window to the world that opens people's thoughts and thought patterns in a more advanced direction and will later compete in the world of work. Quality education is very important to support human development which is based on good learning methods and depends on the learning process at school, so that every student is able to achieve learning goals. One of the important things to achieve this learning is motivation. Learning motivation is an urge that arises from within the student to learn in order to achieve the goals that have been set. Besides that, the teacher's efforts in learning are an important factor in learning success, especially regarding interpersonal communication that teachers have between students. Therefore, this is very important for further research. This research aims to determine the relationship between teacher and student interpersonal communication on student learning motivation. The independent variable in this research is interpersonal communication and the dependent variable is learning motivation. The subjects in this research were students of SMA PGRI 4 Padang City. Validity and reliability testing in this research used the Cronbach's Alpha technique. The hypothesis of this research is that there is a relationship between teacher and student interpersonal communication and student learning motivation.